Mortality in cases of asbestosis diagnosed by a pneumoconiosis medical panel. Issue 2 (February 1987) - Coutts, I I; Gilson, J C; Kerr, I H; Parkes, W R; Turner-Warwick, M
Abstract : One hundred and fifty five male cases of asbestosis certified by the London Pneumoconiosis Medical Panel during 1968-74 were followed up during 1978-9, 4-11 (mean 7.5) years after certification. Fifty nine patients had died, 23 (39%) from lung cancer, 6 (10%) from mesothelioma, and 11 (19%) from other respiratory causes. The number of observed deaths was 2.25 times greater than expected and 7.4 times greater than expected for lung cancer. Adenocarcinoma was the commonest histological type but other cell types were also increased. Finger clubbing (p less than 0.01) and percentage of predicted FEV1 (p less than 0.01) were of value in predicting death, but increasing profusion of small opacities greater than 1/0 (ILO/U-C international classification of radiographs of pneumoconiosis, 1971), duration of exposure to asbestos, time from first exposure to asbestos, and percentage of predicted vital capacity and transfer factor did not predict death.